Electrocatalytic synthesis of ammonia via nitrate reduction under ambient conditions using Pd-CuOx heterostructures - Tan, Joseph Choon Ming (Nanyang Technological University, 2024)
Ammonia is an important fertilizer in agricultural industry, raw material for the chemical industry, and hydrogen carrier for future promising hydrogen industry as a safe storage media. The existing industrial Harber-Bosch process is energy intensive and emits extensive carbon dioxide, as such recent studies have pivoted their attention to electrocatalytic nitrate reduction reaction (NO3RR) as a suitable alternative. Choosing the right catalyst is crucial for NO3RR as a catalyst with high activity and selectivity for nitrate reduction to NH3 and high energy efficiency allows NO3RR to be highly effective for sustainable ammonia synthesis. This project aims to investigate the catalytic performance of Pd-CuOx heterostructure as an electrocatalyst for sustainable ammonia synthesis and to optimize the ammonia synthesis performance via tuning the concentrations of Pd additions and the reduction potentials. The results indicate that Pd-CuOx heterostructures with one quarter of Pd incorporated relative to Cu (denoted as C4P1) exhibit relatively high performance, achieving 47% Faradic efficiency of ammonia at -0.8V vs RHE and ammonia yield rate of 1937µg/h mgcat at -0.9V vs RHE. The synergistic effect between CuOx for promoting the adsorption of nitrate and Pd for facilitating proton adsorption and hydrogenation of N-based intermediates is proposed to contribute to the enhanced catalytic performance. Therefore, the outcome of this study establishes a groundwork for developing high-performance electrocatalysts aimed at addressing the challenges associated with existing methods of ammonia production.